2023
DOI: 10.3390/microorganisms11040891
|View full text |Cite
|
Sign up to set email alerts
|

Use of Microbial Consortia in Bioremediation of Metalloid Polluted Environments

Abstract: Metalloids are released into the environment due to the erosion of the rocks or anthropogenic activities, causing problems for human health in different world regions. Meanwhile, microorganisms with different mechanisms to tolerate and detoxify metalloid contaminants have an essential role in reducing risks. In this review, we first define metalloids and bioremediation methods and examine the ecology and biodiversity of microorganisms in areas contaminated with these metalloids. Then we studied the genes and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 302 publications
0
5
0
Order By: Relevance
“…Recent studies showed the presence of Te and Se in waste products of different industries, which would result in contamination of environment. The bioremediation of these toxic compounds to less toxic elemental forms using these capable yeast strains is promising approach for treatment of metalloid oxyanions present in the industrial effluents instead of less effective and more expensive chemical and physical methods [ 9 , 19 , 23 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed the presence of Te and Se in waste products of different industries, which would result in contamination of environment. The bioremediation of these toxic compounds to less toxic elemental forms using these capable yeast strains is promising approach for treatment of metalloid oxyanions present in the industrial effluents instead of less effective and more expensive chemical and physical methods [ 9 , 19 , 23 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tellurite and selenite pollution is typically treated using a variety of physicochemical techniques, including cutting-edge technologies like ultrafiltration and nanofiltration [ 24 , 25 ]. On the other hand, biological approaches using microorganisms can offer additional benefits for treating these wastewaters since they allow for the biorecovery and production of elemental nanoparticles (NPs) from these pollutants [ 9 , 19 , 23 , 26 ]. A variety of microbial species can transform selenium and tellurium oxyanions through different processes, such as reduction, oxidation, demethylation, and methylation [ 27 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such an artificial consortia, involving cells of microorganisms from different kingdoms [ 13 , 14 , 15 , 16 , 17 ], are especially attractive from a scientific and practical point of view, due to the possibility of expanding its total metabolic potential. At the same time, all the advantages that the artificial consortia of microorganisms themselves have over natural analogues, which have mainly been described in the literature on bacterial cells, are preserved: easy-to-use reproducibility of the compositions of the consortia; the possibility of introducing maximum targeted metabolic activity into the consortia cells, which are improved, including through the genetic modification of cells; targeted variation of the ratios of cell concentrations in the consortium, to regulate the rates of associated biochemical processes catalyzed by cells; sustainable functioning of the created consortia, which are accompanied by increased degrees of conversion of the original substrates, including toxic compounds [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. …”
Section: Introductionmentioning
confidence: 99%
“…sustainable functioning of the created consortia, which are accompanied by increased degrees of conversion of the original substrates, including toxic compounds [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation